2017
DOI: 10.1007/s00586-017-5015-9
|View full text |Cite
|
Sign up to set email alerts
|

Locking stand-alone cages versus anterior plate constructs in single-level fusion for degenerative cervical disease: a systematic review and meta-analysis

Abstract: LSC and APC have similar clinical and radiological outcomes. Further blinded randomised trials are required to establish conclusive evidence in favour of LSC with regards to minimising post-operative dysphagia. We also encourage future studies to make use of formalised dysphagia outcome measures in reporting complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 26 publications
8
51
0
1
Order By: Relevance
“…Their study found that the ZP group had a significantly lower risk of dysphagia. Nambiar et al [31] and Tong et al [32] also found the ZP group achieved a lower incidence of dysphagia after single-level and multi-level fusion, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…Their study found that the ZP group had a significantly lower risk of dysphagia. Nambiar et al [31] and Tong et al [32] also found the ZP group achieved a lower incidence of dysphagia after single-level and multi-level fusion, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…Other reviews showed that despite the higher number of plate technique cases, no significant effect was found regarding the techniques. 22,23 However, in patients in the work by Forgel and McDonnell, 24 who were submitted to surgery to remove plates, high adhesion of the esophagus to the prevertebral and anterior cervical fascias that envelop the plate was observed. 24 All the cases were successful and improved dysphagia of solids and liquids after removal of the plates.…”
Section: Discussionmentioning
confidence: 99%
“…Their study found that the ZP group had a significantly lower risk of dysphagia. Nambiar et al [31] and Tong et al [32] also found that the ZP group achieved a lower incidence of dysphagia after single-level and multilevel fusion, respectively.…”
Section: Subsidencementioning
confidence: 93%